Processes of juridification and defense of water in the southern Andean region of Ecuador - Carlos Quizhpe; Ivette Vallejo (Íconos)
In a context in which mining extractivism is expanding in Latin America, this article deals with the collective action agendas that local populations in the southern Andean region of Ecuador have followed to defend water against the Rio Blanco and Loma Larga projects in Quimsacocha, located in the Cuenca canton, Azuay province. Within such agendas, an injunction was filed in the courts, which obtained a positive ruling and managed to stop the Río Blanco project, and two popular consultations were held – Girón and Cuenca. These experiences are part of what we will call processes of juridification in defense of water, in which visions and ontologies about the human-nature relationship are disputed. To compile information, we resorted to in-depth interviews with community members and members of ecological collectives, social mapping and document review. This article discusses the complexity of the demands against mega-mining in legal terms and the power dynamics that are interwoven in the enforceability of collective rights and the rights of nature. It also analyzes the support offered in the legal sphere to processes of juridification by mobilization actions that take place in parallel. The article contributes to critical debates on environmental justice and water justice.